Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Catering Ar-Risalah di Kota Bekasi - Febi Rahmawati; Hadita Hadita; Neng Siti Komariah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
Currently, many Micro, Small and Medium Enterprises are taking part in the culinary sector. In West Java, especially the city of Bekasi, people engaged in Micro, Small and Medium Enterprises in the culinary world (catering) are not difficult to find. The large number of actors involved in the culinary world in the city of Bekasi has made competition between Micro, Small and Medium Enterprises increasingly tight. The presence of Ar-Risalah Catering services can make it easier to fulfill needs at every event, especially for customers who don't want to bother with providing food and food service at parties or events. The purpose of this research is to find out whether there is an influence of Product Quality and Service Quality on Customer Satisfaction at Ar-Risale Catering in Bekasi City. The research uses quantitative methods through questionnaires and data from the results of the questionnaire will be processed and tested using SPSS 27 Version. Based on the results of this research, it is concluded that Product Quality and Service Quality have a partially significant effect on Customer Satisfaction.